Exploration of new innovation scenarios through the reinterpretation of local material culture in the master in design - Martins, Jo?o (2022)
Our Master's Degree in Integrated Design is a teaching project designed to protect, predominantly, a series of professional specializations. It is a precursor to the mission of the educational institution where it works, namely in its search for the economic, social impact and cultural in the region where it is inserted. This cycle of studies leading to the master's degree lasts for three semesters and integrates a specialization course consisting of a set of curricular units taught in the first two school levels, which includes a curricular unit of the Integrated Project Laboratory. The theme of this year's project challenged the students to develop new perspectives on the local Tableware whose style that has contributed to the characterization of the city's identity. From the concept of contemporaneity, and the idea of the need for a "new filling" for a "new architecture", in keeping with the new aesthetic-functional and symbolic requirements of its inhabitants, the project aimed to contribute to the recovery of the image of the city as an important center of dynamization of an industrial sector with tradition in the region. In establishing partnerships with entities and companies, the teaching team intended to provide students with various contacts that enrich their knowledge about the subject. In this sense, the project work was supported by the City Museum, City Hall, Industries of the Region and professionals in various areas of Design and related (architecture, engineering, anthropology, etc.). The realization of the project in design implied a phased work process from the research on the problem, through the generation of ideas until its materialization. During this work, the use of supports, tools and techniques associated to the Design Process was made so as to obtain results in each of the phases that together directed the project to a solution based on reasoned argumentation. In the end, the project showed that the dishes drawn here may in the future achieve great notoriety as a result of the good interpretation of the material culture that preceded them, and the quality of their design. It is concluded that the recovery of the history of the city's ceramics can contribute to stimulate more innovation and creativity in the future.